Unpacking the Theory Behind One Health Food Safety Programs: A Vietnam Case Study - Lam, Steven; Nguyen, Huyen Thi Thu; Tuan, Hai Ngo Hoang; Nguyen, Luong Thanh; Nguyen-Viet, Hung; Toribio, Jenny-Ann; Thanh, Huyen Le Thi; Pham-Van, Hung; Grace, Delia; Unger, Fred (Frontiers in Veterinary Science, 2021)
Many One Health programs are inherently complex, characterized by multiple perspectives from multiple sectors, delivery across various scales, and a focus on complex problems at the convergence of people, animals, and the environment. This complexity makes them difficult to conceptualize, requiring frameworks to organize the different program components. Evaluation frameworks that unpack the sequence of events linking program activities to outcomes (e.g. Theory of Change) and track outcomes (e.g. Outcome Mapping) show promise in supporting the development of One Health programs. While widely used in international development and health contexts, there has been little reflection on the use of Theory of Change and Outcome Mapping within One Health efforts. This paper reflects on the process of applying these frameworks to conceptualize a One Health food safety program in Vietnam. We find Theory of Change fostered the characterization of a change pathway toward safer pork, while Outcome Mapping kept us informed of where along the change pathway we were. One Health programs considering evaluation frameworks should adopt elements that make sense to them, be intentional about co-designing the evaluation, and view evaluation as a process, not a product.